Novel half‐life extended anti‐MIF nanobodies protect against endotoxic shock. Issue 6 (25th January 2018) - Sparkes, Amanda; De Baetselier, Patrick; Brys, Lea; Cabrito, Inês; Sterckx, Yann G.-J.; Schoonooghe, Steve; Muyldermans, Serge; Raes, Geert; Bucala, Richard; Vanlandschoot, Peter; Van Ginderachte, Jo A.; Stijlemans, Benoît
ABSTRACT: Sepsis—leading to septic shock—is the leading cause of death in intensive care units. The systemic inflammatory response to infection, which is initiated by activated myeloid cells, plays a key role in the lethal outcome. Macrophage migration inhibitory factor (MIF) is an upstream immunoregulatory mediator, released by myeloid cells, that underlies a common genetic susceptibility to different infections and septic shock. Accordingly, strategies that are aimed at inhibiting the action of MIF have therapeutic potential. Here, we report the isolation and characterization of tailorable, small, affinity‐matured nanobodies (Nbs; single‐domain antigen‐binding fragments derived from camelid heavy‐chain Abs) directed against MIF. Of importance, these bioengineered Nbs bind both human and mouse MIFs with nanomolar affinity. NbE5 and NbE10 inhibit key MIF functions that can exacerbate septic shock, such as the tautomerase activity of MIF (by blocking catalytic pocket residues that are critical for MIF's conformation and receptor binding), the TNF‐inducing potential, and the ability of MIF to antagonize glucocorticoid action. A lead NbE10, tailored to be a multivalent, half‐life extended construct (NbE10‐NbAlb8‐NbE10), attenuated lethality in murine endotoxemia when administered via single injection, either prophylactically or therapeutically. Hence, Nbs, with their structural and pharmacologic advantages over currently available inhibitors, may be an effective, novel approach to interfere with the action of MIF in septic shock and other conditions of inflammatory endorgan damage.—Sparkes, A., De Baetselier, P., Brys, L., Cabrito, I., Sterckx, Y. G.‐J., Schoonooghe, S., Muyldermans, S., Raes, G., Bucala, R., Vanlandschoot, P., Van Ginderachter, J. A., Stijlemans, B. Novel half‐life extended anti‐MIF nanobodies protect against endotoxic shock. FASEB J. 32, 3411–3422 (2018). www.fasebj.org